Response surface methodology and repeated-batch fermentation strategies for enhancing lipid production from marine oleaginous Candida parapsilosis Y19 using orange peel waste - AbdAllah M. Matouk; Gadallah M. Abu-Elreesh; Mohamed Ali Abdel-Rahman; Said E. Desouky; Amr H. Hashem (Microbial Cell Factories)
Abstract Oleaginous yeasts are considered promising sources for lipid production due to their ability to accumulate high levels of lipids under appropriate growth conditions. The current study aimed to isolate and identify oleaginous yeasts having superior ability to accumulate high quantities of lipids; and enhancing lipid production using response surface methodology and repeated-batch fermentation. Results revealed that, twenty marine oleaginous yeasts were isolated, and the most potent lipid producer isolate was Candida parapsilosis Y19 according to qualitative screening test using Nile-red dye. Orange peels was used as substrate where C. parapsilosis Y19 produced 1.14 g/l lipids at 23.0% in batch fermentation. To enhance the lipid production, statistical optimization using Taguchi design through Response surface methodology was carried out. Total lipids were increased to 2.46 g/l and lipid content increased to 30.7% under optimal conditions of: orange peel 75 g/l, peptone 7 g/l, yeast extract 5 g/l, inoculum size 2% (v/v), pH 5 and incubation period 6 d. Furthermore, repeated-batch fermentation of C. parapsilosis Y19 enhanced lipid production where total lipids increased at 4.19 folds (4.78 g/l) compared to batch culture (before optimization). Also, the lipid content was increased at 1.7 folds (39.1%) compared to batch culture (before optimization). Fatty acid profile of the produced lipid using repeated-batch fermentation includes unsaturated fatty acids (USFAs) at 74.8% and saturated fatty acids (SFAs) at 25.1%. Additionally, in repeated-batch fermentation, the major fatty acid was oleic acid at 45.0%; followed by linoleic acid at 26.0%. In conclusion, C. parapsilosis Y19 is considered a promising strain for lipid production. Also, both statistical optimizations using RSM and repeated-batch fermentation are efficient methods for lipid production from C. parapsilosis Y19.